Healthcare professionals' attitudes concerning prioritisation decisions: a quali-quantitative analysis in Angola - Pinho, Micaela (2021)
Bedside rationing decisions are a necessary evil in the context of resource scarcity. The ethical values inherent in decisions about who to treat make interprofessional collaboration between health professionals essential. We evaluate and compare the attitudes of Angolan physicians and nurses towards patient’s prioritisation decisions and the rationing principles supported. Faced with rationing scenarios comprising of four-patient respondents should: 1) select the only patient to treat, explaining their choice; 2) establish a patient care sequential order. Non-parametric tests and multinomial logistic regressions were performed to compare patient’s choice between both groups and explore relations between socio-demographic, health and health-related behaviours and patient top priority assigned. Content analysis was used to explore the reasons for patients’ selection. Findings suggest that physicians and nurses share similar views, suggesting no tensions regarding patient’s prioritisation. Respondents support health maximisation, severity and fair-innings as rationing principles while waiting time and health-related behaviours were undervalued.